Use of Remdesivir in children with COVID-19: report of an Italian multicenter study - Lorenza Romani; Marco Roversi; Stefania Bernardi; Elisabetta Venturini; Silvia Garazzino; Daniele Donà; Andrzej Krzysztofiak; Carlotta Montagnani; Elisa Funiciello; Francesca Ippolita Calò Carducci; Caterina Marabotto; Elio Castagnola; et al. (BMC, 2024)
Abstract Background COVID-19 is generally milder in children than in adults, however severe infection has been described in some patients. Few data are available on use of Remdesivir (RDV) in children, as most clinical trials focused on adult patients. We report a multicenter study conducted in 10 Italian Hospitals to investigate the safety of RDV in children affected by COVID-19. Methods We collected the clinical data of children with COVID-19 treated with RDV between March 2020 and February 2022 in 10 Italian hospitals. Clinical data were compared according to a duration of RDV therapy more or less than 5 days. Linear regression model was used to determine the association of significant variables from the bivariate analysis to the duration of RDV therapy. Results A total of 50 patients were included, with a median age of 12.8 years. Many patients had at least one comorbidity (78%), mostly obesity. Symptoms were fever (88%), cough (74%) and dyspnea (68%). Most patients were diagnosed with pneumonia of either viral and/or bacterial etiology. Blood test showed leukopenia in 66% and increased C-reactive protein (CRP) levels in 63% of cases. Thirty-six patients received RDV for 5 days, nine patients up to 10 days. Most children who received RDV longer were admitted to the PICU (67%). Treatment with RDV was well tolerated with rare side effects: bradycardia was recorded in 6% of cases, solved in less than 24 h after discontinuation. A mild elevation of transaminases was observed in 26% of cases, however for the 8%, it was still detected before the RDV administration. Therefore, in these cases, we could not establish if it was caused by COVID-19, RDV o both. Patients who received RDV for more than 5 days waited longer for its administration after pneumonia diagnosis. The presence of comorbidities and the duration of O2 administration significantly correlated with the duration of RDV therapy at the linear regression analysis. Conclusion Our experience indicates that RDV against SARS-CoV-2 is safe and well-tolerated in pediatric populations at high risk of developing severe COVID-19. Our data suggest that delaying RDV therapy after diagnosis of pneumonia may be associated with a longer duration of antiviral therapy, especially in patients with comorbidities.